Transformasi Tradisi Dalam Teater Piktografik Putu Wijaya - Benny Yohanes (LP2M ISBI Bandung, 2012)
ABSTRACTThis article considers the fundamental premise of realism methodology that theory has a ground in social basic structures. Factual reality, including the artistic form creation, can be seen as referential background for theory formation. Theory draws its coherence from its referent. By using the epistemic mode of realism methodology, which combines religion and myth theory, this article illustrates Putu Wijaya’s theatrical creations through a causal and deep interpretation. The aim of analysis is to know and to reveal what is underneath that exist behind Putu Wijaya’s theatre performance. The result of the research shows that Putu Wijaya’s aesthetic choice that manifested as mental terror theatre is understood as the process of replication. This replication process aims at inventing pictographic representation as a way to transform tradition.Key words : deep interpretation, transformation, pictographic theatre ABSTRAKArtikel ini membahas premis dasar metodologi realisme bahwa teori memiliki dasar dalam struktur dasar sosial. Realitas faktual, termasuk penciptaan bentuk artistik, dapat dilihat sebagai latar belakang referensial untuk pembentukan teori. Teori menarik koherensinya dari rujukan. Dengan menggunakan modus epistemis metodologi realisme, yang menggabungkan agama dengan teori mitos, artikel ini menggambarkan kreasi teater Putu Wijaya melalui interpretasi kausal dan mendalam. Tujuan dari analisis adalah untuk mengetahui dan mengungkapkan apa yang ada di balik pertunjukan teater Putu Wijaya. Hasil dari penelitian menunjukkan bahwa pilihan estetika Putu Wijaya yang dinyatakan sebagai teater teror mental dipahami sebagai proses replikasi. Proses replikasi bertujuan untuk menciptakan representasi piktografik sebagai sebuah cara untuk mengubah tradisi.Kata kunci: interpretasi mendalam, transformasi, teater piktografik